Dynamic impact of liver allocation policy change on donor utilization. Issue 7 (9th March 2022) - Chan, Ethan; Logan, April J.; Sneddon, Jeffrey M.; Singh, Navdeep; Brock, Guy N.; Washburn, William K.; Schenk, Austin D.
Abstract : Liver allocation policy was changed to reduce variance in median MELD scores at transplant (MMaT) in February 2020. "Acuity circles" replaced local allocation. Understanding the impact of policy change on donor utilization is important. Ideal (I), standard (S), and non‐ideal (NI) donors were defined. NI donors include older, higher BMI donors with elevated transaminases or bilirubin, history of hepatitis B or C, and all DCD donors. Utilization of I, S, and NI donors was established before and after allocation change and compared between low MELD (LM) centers (MMaT ≤ 28 before allocation change) and high MELD (HM) centers (MMaT > 28). Following reallocation, transplant volume increased nationally (67 transplants/center/year pre, 74 post, p .0006) and increased for both HM and LM centers. LM centers significantly increased use of NI donors and HM centers significantly increased use of I and S donors. Centers further stratify based on donor utilization phenotype. A subset of centers increased transplant volume despite rising MMaT by broadening organ acceptance criteria, increasing use of all donor types including DCD donors (98% increase), increasing living donation, and transplanting more frequently for alcohol associated liver disease. Variance in donor utilization can undermine intended effects of allocation policy change. Abstract : The authors critically examine center‐level utilization of donor livers following allocation policy change and find widely disparate utilization of available donor organs.